Assistance for the Preparation of Regulations on Livestovk Management in Teratak Rendah Village - Seprido; Afrinald Rizhan; Desriadi Desriadi (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Service regarding assistance in drafting Teratak Rendah village regulations regarding livestock management in Logas Tanah darat District, Kuantan Singingi regency. Drafting village regulations is one of the main tasks and functions of the village consultative body so the aim of this service is to assist the BPD of teratak Rendah village in drafting village regulations regarding livestock management. This service activity is carried out using the mentoring method. The result of this service activity is the preparation of Teratak Rendah regulations regarding livestock management that follow the standard rules for drafting village regulations. This preparation went through several stages, namely : planning meeting; preparation; arrangement of language in draft village regulations; village meetings; revision of draft village regulations; deliberation to determine and sign the darft of Teratak Rendah regulations. The formation of Teratak Rendah village regulations regarding the management of livestock has taken into account the requirements of a good statutory regulation, both regarding the principles, substance and techniques of its formation.